Entrepreneurial orientation and start-ups performance: The role of entrepreneurial self-efficacy - Nson, Yilkes Danladi (Annals of Management and Organization Research, 2025)
Purpose: This study examines how entrepreneurial orientation and entrepreneurial self-efficacy interact to identify and create entrepreneurial opportunities for start-ups a successful business in North Central Nigeria. Research Methodology: Primary data were collected using questionnaires from a sample size of 354 SMEs owners and  analyzed using PLS-SEM version 4.1.0.4. Results: The results indicated significant positive relationships between EO and SP, EO and ESU, ESU and SP, EO and EOP, and EOP and SP. Mediation analysis revealed partial mediation of EOP and ESU on the relationship between EO and SP. The moderation analysis revealed that with an increase in ESE, the relationship between EO and SP is strengthened; ESE does not moderate the relationship between EO and ESU; higher ESE weakens the positive impact of ESU on SP, while a higher value of ESE results in a stronger relationship between EOP and SP, as depicted in graph 1-4. Limitations: The study is limited to entrepreneurial orientation, self-efficacy, opportunities, and startups in North Central Nigeria. Contribution: This study provides valuable insights to policymakers in entrepreneurship to create a holistic orientation policy that will ensure that people see the need and opportunities to engage in farming in order to ensure profits for the individual and food availability for the majority population. Originality: This is the first study in Nigeria (Africa) to test how entrepreneurial orientation and self-efficacy interact to identify and create opportunities to start a successful business.